THE ROLE OF THE CISG IN CANADIAN CONTRACT PRACTICE: AN EMPIRICAL STUDY - Coyle, John F (Journal of Law and Commerce, 2020)
In much of the legal literature, the fact that the United Nations Convention on Contracts for the International Sale of Goods (CISG) has been ratified by so many nations constitutes incontrovertible evidence of its success. This narrative fails to account, however, for the fact that private parties can choose to exclude the CISG from their international sales contracts. This Article draws upon a hand-collected dataset of contracts executed by public companies in Canada to show that these companies overwhelmingly choose to exclude the CISG from their international sales agreements. It also shows that these same companies are frequently unaware that selecting the law of a Canadian province can result in the application of the CISG and that few (if any) of these companies consciously select the CISG by selecting provincial law. While the Article turns up a few tantalizing hints that attorneys practicing in Quebec may be slightly more receptive to the CISG than attorneys practicing in the rest of Canada, the overall portrait that emerges is of a nation where this treaty is excluded by sophisticated actors in almost all cases. This finding raises important questions of whether the CISG is achieving its intended purpose of facilitating international trade.